Germanium quantum well with two subbands occupied: kinetic properties - Berkutov, I.B.; Andrievskii, V.V.; Komnik, Yu.F.; Mironov, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Multisubband transport of the p-type Si0.4Ge0.6/Ge/Si0.4Ge0.6 heterostructure has been investigated by means of magnetotransport measurements at low temperatures and high magnetic fields. Two frequency Shubnikov–de Haas oscillations indicate occupation of two subbands. This allows us to determine the densities and mobilities of the charge carriers on each subband. Shubnikov–de Haas oscillations reveal two 2D conduction subbands with carrier effective masses of 0.112m0 and 0.131m0. The quantum Hall ferromagnetic states which results from the crossing of two Landau levels with opposite spin and different subband was observed in SiGe systems for the first time.